DINAMIKA PEMILU SERENTAK PADA KPPS KELURAHAN SAMATA KECAMATAN SOMBA OPU KABUPATEN GOWA 2024 - Mirfan, Mirfan; Syarifuddin, Syarifuddin; Zulhaji, Zulhaji (Politeknik Perkeretaapian Indonesia Madiun, 2024)
The 2024 Simultaneous General Election in Samata Village, Somba Opu District, Gowa Regency, is an important momentum to evaluate the dynamics and effectiveness of the work of the Voting Organizer Group (KPPS) in carrying out the democratic process at the local level. The purpose of this study is to identify the challenges and obstacles faced by the Voting Organizer Group (KPPS) in implementing the simultaneous election in the area. to evaluate the role and contribution of KPPS in maintaining transparency, accountability, and justice during the simultaneous general election process in Samata Village. to assess the level of voter participation in Samata Village and the factors that influence this participation during the simultaneous election. The results of the study indicate that the implementation of the 2024 Simultaneous Election in Samata Village went well despite facing a number of challenges. These challenges include the quality of the smartphone camera used to document the C1 plano results, the lack of understanding of some voters regarding election procedures, differences in the terms Permanent Voter List (DPT), Additional Voter List (DPTb), and Special Voter List (DPK). The active role of the Voting Organizing Group (KPPS) has proven to be very important in overcoming these obstacles and ensuring the smooth running of the voting and vote counting process. KPPS has succeeded in ensuring that every stage of the election can be carried out properly and orderly.